Attitudes towards climate change migrants - Marc Helbling (Climatic Change, 2020)
While climate change has become a salient political and social issue in Western societies, we know relatively little about how these societies will react to one of the potentially important consequences of climate change: increasing migration flows. By means of a representative online survey in Germany, this paper therefore investigates for the very first time to what extent citizens in industrialized societies are willing to accept climate change migrants, especially in comparison with other groups of migrants and refugees, and the circumstances and principles under which they would accept them. The findings show that climate change migrants receive high support levels comparable with those enjoyed by political refugees (migrants who need special protection) and that contrast with attitudes towards economic migrants (who are often not seen as in need of special protection). We also see that people are more likely to accept justifications for taking climate change migrants when they realize that the expected number of migrants is relatively low. While arguments about morality, corrective justice, and a country's capacity lead to similar acceptance rates in general, the latter argument plays a more important role for highly educated people and non-environmentalists than the former two. The findings of this study allow us to better prepare for potential conflicts that might emerge with increasing migration flows caused by climate change.
Keywords: 300; climate change; migration; prejudices